Happiness - Kumar, Prashant (International Journal of Psychosocial Rehabilitation, 2020)
Every human being wants to live happily in this world. It is the internal happiness that matters most than the external happiness, which is due to material objects. There are various factors that affect the happiness of an individual. Possessing good health is the first and foremost factor affecting happiness. Healthy people are happier than unhealthy people. Taking a proper and balanced nutritional diet is also responsible for happiness. Doing regular physical and mental exercise is a must for good health, resulting in a happy being. One has to be honest and truthful throughout his/her life. One has to be positive, honest, and truthful in all his/her thinking and actions. Forgiveness is a great quality to lead a happy life. Life is uncertain, so one has to live in the present moment. Life is lived moment by moment, day by day. One has to accept the uncertainties of life. For a happy life, ego, i.e., the false sense of self, is to be transcended. Finally, for living happily, one has to live life himself/herself, so love yourself first and live life the way you feel it is to be lived, not on what others say or what society thinks.